From smartphones to phantom limbs : examining how the smartphone constitutes the self in Singaporean millenials - Cheah, Dionne Wei Lin (2016)
As Singapore’s smartphone adoption rates is among the highest in the world, local Millenials are not only increasingly adopting smartphones but using them heavily. Besides facilitating communication, the multi-functionality of the device augments digital practices of users. Individuals have grown increasingly attached to their smartphones, to the extent that it has been viewed as an ‘extension of the self/body’. This paper aims to explore how the use of smartphone is embbeded in the everyday lives of local Millenials and how it constitutes the self. The theoretical framework relies upon the domestication approach and cyborg theory to analyse the phenomenon. By primarily focusing on the frequency of use, context of use and user dependency on the smartphone, this paper shows how the self is embodied within the smartphone vis-à-vis common digital practices that Millenials engage in and their percieved relationship with device. The cyborgian relationship between Millenials and their smartphones is elucidated.